Impact of an Intervention to Control Imipenem-Resistant Acinetobacter baumannii and Its Resistance Mechanisms: An 8-Year Survey - Chen, Lida; Tan, Pinghai; Zeng, Jianming; Yu, Xuegao; Cai, Yimei; Liao, Kang; Guo, Penghao; Chen, Yili; Wu, Zongwen; Qu, Pinghua; Cai, Renxin; Chen, Cha; et al. (Frontiers in Microbiology, 2021)
Background: This study aimed to examine the impact of an intervention carried out in 2011 to combat multi-drug resistance and outbreaks of imipenem-resistant Acinetobacter baumannii (IRAB), and to explore its resistance mechanism. Methods: A total of 2572 isolates of A. baumannii, including 1673 IRAB isolates, were collected between 2007 and 2014. An intervention was implemented to control A. baumannii resistance and outbreaks. Antimicrobial susceptibility was tested by calculating minimal inhibitory concentrations (MICs), and outbreaks were typed using pulsed-field gel electrophoresis (PFGE). Resistance mechanisms were explored by polymerase chain reaction (PCR) and whole genome sequencing (WGS). Results: Following the intervention in 2011, the resistance rates of A. baumannii to almost all tested antibiotics decreased, from 85.3% to 72.6% for imipenem, 100% to 80.8% for ceftriaxone, and 45.0% to 6.9% for tigecycline. The intervention resulted in a decrease in the number (seven to five), duration (8 to 3 months), and departments (five to three) affected by outbreaks; no outbreaks occurred in 2011. After the intervention, only blaAMPC (76.47% to 100%) and blaTEM-1 (75.74% to 96.92%) increased (P < 0.0001); whereas blaGES-1 (32.35% to 3.07%), blaPER-1 (21.32% to 1.54%), blaOXA-58 (60.29% to 1.54%), carO (37.50% to 7.69%), and adeB (9.56% to 3.08%) decreased (P < 0.0001). Interestingly, the frequency of class B β-lactamase genes decreased from 91.18% (blaSPM-1) and 61.03% (blaIMP-1) to 0%, while that of class D blaOXA-23 increased to 96.92% (P < 0.0001). WGS showed that the major PFGE types causing outbreaks each year (type 01, 11, 18, 23, 26, and 31) carried the same resistance genes (blaKPC-1, blaADC-25, blaOXA-66, and adeABC), AdeRS mutations (G186V and A136V), and a partially blocked porin channel CarO. Meanwhile, plasmids harboring blaOXA-23 were found after the intervention. Conclusions: The intervention was highly effective in reducing multi-drug resistance of A. baumannii and IRAB outbreaks in the long term. The resistance mechanisms of IRAB may involve genes encoding β-lactamases, efflux pump overexpression, outer membrane porin blockade, and plasmids; in particular, clonal spread of blaOXA-23 was the major cause of outbreaks. Similar interventions may also help reduce bacterial resistance rates and outbreaks in other hospitals.